Immune-related gene expression in Penaeus vannamei fed Aloe vera - Trejo-Flores,José Vladimir (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2018)
ABSTRACT The immune response is critical in cultured shrimp facing pathogens that are serious concerns. Therefore, immune-related gene expression was investigated in Penaeus vannamei fed with Aloe vera. Shrimp weighing 2.9 ± 0.8 g were fed with 1 g of A. vera kg feed−1. Six shrimp were sampled at 0, 6, 12, 24, 48, and 72 h for gene expression. Samples of time zero were taken just before feeding with aloe. After feeding with aloe during 24 h, uneaten food and waste material were removed and then shrimp were fed only with commercial feed. Quantitative real-time PCR measured time series expression of four genes (translationally controlled tumor protein [TCTP], superoxide dismutase [SOD], heat shock protein 70 [HSP70], and penaeidin4). The expression of TCTP was down-regulated, and the expression of SOD, HSP70, and penaeidin4 was up-regulated. This is the first report showing the effect of A. vera on the modulation of shrimp immune response. The immunostimulant properties of A. vera could be useful for cultured shrimp health.